2003
DOI: 10.1088/0264-9381/20/23/008
|View full text |Cite
|
Sign up to set email alerts
|

All supersymmetric solutions of minimal supergravity in six dimensions

Abstract: A general form for all supersymmetric solutions of minimal supergravity in six dimensions is obtained. Examples of new supersymmetric solutions are presented. It is proven that the only maximally supersymmetric solutions are flat space, AdS 3 × S 3 and a plane wave. As an application of the general solution, it is shown that any supersymmetric solution with a compact horizon must have near-horizon geometry R 1,1 ×T 4 , R 1,1 ×K3 or identified AdS 3 × S 3 .

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
458
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(468 citation statements)
references
References 63 publications
(178 reference statements)
9
458
0
1
Order By: Relevance
“…In the ungauged theory considered in [33] it was shown that these equations can be completely solved when H is compact and the near-horizon geometry can therefore be determined explicitly. This has also been done in the minimal six-dimensional ungauged supergravity [28].…”
Section: General Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the ungauged theory considered in [33] it was shown that these equations can be completely solved when H is compact and the near-horizon geometry can therefore be determined explicitly. This has also been done in the minimal six-dimensional ungauged supergravity [28].…”
Section: General Analysismentioning
confidence: 99%
“…In the ungauged theories considered in [33] and [28] it was shown that, when H is compact, ∆ must be constant on H and that H must admit a Killing vector. We have been unable to establish the same results in the gauged theory.…”
Section: Jhep02(2004)006mentioning
confidence: 99%
“…One may also think of this in terms of a compactification of the D1-D5-P system in IIB supergravity on a four-torus. The BPS equations of this system were first extracted in [23,24] but the form seemed hopelessly nonlinear at all levels. In spite of this, one could construct a limited set of non-trivial solutions using spectral flow techniques [25,26].…”
Section: Jhep10(2013)137mentioning
confidence: 99%
“…In the six-dimensional theory, the graviton multiplet contains a self-dual tensor field and so the entire bosonic sector consists of the graviton, the dilaton and an unconstrained 2-form gauge field with a 3-form field strength. The BPS equations of this theory were constructed in [23,24] and in [18] it was shown that the BPS system could be dramatically simplified and that most of the equations could be reduced to a linear system. We now review this structure in some detail.…”
Section: The Bps Solutions In Six Dimensionsmentioning
confidence: 99%
“…We would like to shed some light on the relation between the DW solutions (and their deformations) and the classification methods developed in [53], and successfully applied to supergravity theories with 8 supercharges in [54,55,56,57,58,59,60,61,60,62,63,30,64,31]. In particular we want to understand within the framework of the classification, in which class the solutions we are study fall in.…”
Section: Domain Wall and Classificationmentioning
confidence: 99%